Pengembangan Multimedia PANDACA (Pandai Tanda Baca) untuk Siswa Sekolah Dasar - Anindia Nur Amalia; Ida Putriani; Adin Fauzi (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
The aims of this research is to describe feasibility and legibility of developing PANDACA (Smart Punctuation) multimedia for elementary school students. This study used Research and Development (RnD) research method owned by Borg and Gall which was adopted by Sugiyono. The subjects in this study is teachers and students grades 1 to 6 at UPT SD Negeri Garum 01 who were selected by random sampling technique. The percentage results of media validation according to experts are: 1) material experts 91.67%, 2) media experts 92.36%, and 3) linguists 90.83%. The results obtained state that the PANDACA multimedia (Smart Punctuation) is very good and feasible to use. In addition, the results of the readability test showed that the percentage of teachers was 95.83% and students 93.33%. The results obtained stated that the PANDACA multimedia (Smart Punctuation) was very good and legible. The percentage value obtained from the results of feasibility and readability, the PANDACA multimedia (Smart Punctuation) can be used as a learning medium for teachers and students in deepening material and understanding of the use of good and correct punctuation.